Reinventing Prevention : Why Did 'Crime Prevention' Develop So Late? - O'Malley, Pat (The British journal of criminology, 2007)
While crime prevention is taken to exemplify governance in the risk society', it may represent a retarded example of risk-based urban security. Crime prevention was unaffected by risk-based prevention characteristic of much nineteenth-century government of this domain. The development of risk-based fire prevention, by contrast, was substantially in place at the turn of the twentieth century, promoted by the convergence of insurance and other interests in securing property. Rather than seeing crime prevention as exemplifying the move toward the risk society' thesis, it may be better understood as a case in which neo-liberal governance and insurance technologies transformed a domain of governance that had been unusually resistant to risk-based approaches